2020
DOI: 10.21037/atm-20-2502a
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance induction with donor hematopoietic stem cell infusion in kidney transplantation: a single-center experience in China with a 10-year follow-up

Abstract: Background: Immunosuppressive therapy after life-saving kidney transplantation increases the risk of infection, cardiovascular diseases, metabolic diseases, and cancer. To date, four centers (three in the USA and one in South Korea) have reported clinical tolerance trials in kidney transplantation. We performed the first Chinese clinical trial in which kidney transplantation was combined with donor hematopoietic stem cell (DHSC) infusion to induce tolerance. This study summarizes the 10-year follow-up results.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Among these, mesenchymal stem cells (MSCs) are considered to be one of the most promising types of cells for cellular therapy because of their ease of harvesting, low immunogenicity, and ability to be stored and expanded in vitro (15,16). Notably, numerous preclinical and clinical studies have confirmed the potential role of MSCs in kidney protection and repair (17)(18)(19)(20)(21)(22). However, the mechanisms by which MSCs exert their therapeutic effects remain controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, mesenchymal stem cells (MSCs) are considered to be one of the most promising types of cells for cellular therapy because of their ease of harvesting, low immunogenicity, and ability to be stored and expanded in vitro (15,16). Notably, numerous preclinical and clinical studies have confirmed the potential role of MSCs in kidney protection and repair (17)(18)(19)(20)(21)(22). However, the mechanisms by which MSCs exert their therapeutic effects remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms by which MSCs exert their therapeutic effects remain controversial. Researchers previously believed that MSCs replaced injured cells through differentiation after introduction into the body, but this view was challenged by the fact that MSCs disappeared from the injured kidney and other organs within 72 h after administration, suggesting that differentiation and replacement of damaged cells by stem cells is probably a rare and late event in AKI in vivo (22,23).…”
Section: Introductionmentioning
confidence: 99%